Management of type 2 diabetes in young adults aged 18–30 years: ADS/ADEA/APEG consensus statement. Issue 8 (17th April 2022) - Wong, Jencia; Ross, Glynis P; Zoungas, Sophia; Craig, Maria E; Davis, Elizabeth A; Donaghue, Kim C; Maple‐Brown, Louise J; McGill, Margaret J; Shaw, Jonathan E; Speight, Jane; Wischer, Natalie; Stranks, Stephen
Abstract: Introduction: Type 2 diabetes in young adults (nominally, 18–30 years of age) is a more aggressive condition than that seen in older age, with a greater risk of major morbidity and early mortality. This first Australian consensus statement on the management of type 2 diabetes in young adults considers areas where existing type 2 diabetes guidance, directed mainly towards older adults, may not be appropriate or relevant for the young adult population. Where applicable, recommendations are harmonised with current national guidance for type 2 diabetes in children and adolescents (aged < 18 years). The full statement is available at https://www.diabetessociety.com.au, https://www.adea.com.au and https://www.apeg.org.au . Main recommendations: Advice is provided on important aspects of care including screening, diabetes type, psychological care, lifestyle, glycaemic targets, pharmacological agents, cardiovascular disease risk management, comorbidity assessment, contraception and pregnancy planning, and patient‐centred education. Special considerations for Aboriginal and Torres Strait Islander Australians are highlighted separately. Changes in management as a result of this statement: Management recommendations for young adults, which differ from those for adults, include: ▪ screening for diabetes in young adults with overweight or obesity and additional risk factors, including in utero exposure to type 2 diabetes or gestational diabetes mellitus; ▪ more stringent glucose targets (glycated haemoglobin ≤ 6.5% [≤ 48 mmol/mol]); ▪ in the context of obesity or higher cardio‐renal risk, glucagon‐like peptide 1 receptor agonists and sodium–glucose cotransporter 2 inhibitors are preferred second line agents; ▪ β‐cell decline is more rapid, so frequent review, early treatment intensification and avoidance of therapeutic inertia are indicated; ▪ a blood pressure target of < 130/80 mmHg, as the adult target of ≤ 140/90 mmHg is too high; ▪ absolute cardiovascular disease risk calculators are not likely to be accurate in this age group; early statin use should therefore be considered; and ▪ a multidisciplinary model of care including an endocrinologist and a certified diabetes educator.